Correlation between frictional force and surface roughness of orthodontic archwires. Issue 6 (27th May 2015) - Choi, Samjin; Hwang, Eun‐Young; Park, Hun‐Kuk; Park, Young‐Guk
Summary: Lateral force microscopy measures the lateral bending of the cantilever depending on the frictional force acting between the tip and surface. The aim of this study was to investigate and compare the relationship between the surface roughness and frictional resistance of four archwire and bracket combinations consisting of the 0.016‐inch NiTi and 0.019 × 0.025‐inch stainless steel archwires interacting clinically with two representative self‐ligating brackets, active‐type Clippy‐C ® ceramic self‐ligating brackets, and passive‐type Damon ® stainless steel self‐ligating brackets, using the lateral force microscopy technique. A 0.016‐inch NiTi archwire interacting with passive‐type Damon ® stainless steel self‐ligating brackets showed the smoothest surface roughness and the lowest frictional resistance compared to other combinations. The archwires interacting with passive‐type Damon ® stainless steel self‐ligating brackets showed significantly lower surface roughness and frictional resistance than those interacting with active‐type Clippy‐C ® ceramic self‐ligating brackets. The frictional force in the in vivo archwire and bracket system increased with increasing surface roughness of the archwire. This positive correlation suggests that surface roughness can be used as an evaluating marker for estimating the efficiency of orthodontic treatment, rather than the direct measurement of frictional force. SCANNING 37:399–405, 2015. © 2015 Wiley Periodicals, Inc.